A study on the key characteristics of the explosive mixture ocfol-5.5 - Nguyen Trong, Đại (Journal of Military Science and Technology, 2024)
HMX is currently one of the most powerful explosives. However, HMX has the drawbacks of being sensitive to impact and friction, having poor compressibility, and being difficult to directly load into various types of weapons. Ocfol-5.5 is a phlegmatized version of HMX, primarily composed of HMX (94-96%) and phlegmatizing agents (4-6%). This paper presents the results achieved in the research and development of Ocfol-5.5, the selection of phlegmatizing agents, and the orientation of the manufacturing technology. Optimal manufacturing parameters were selected in a laboratory setting. HMX was phlegmatized using a mixture of stearic acid (38%), ceresin (60%), and Sudan yellow pigment (2%). The phlegmatizing process was carried out by dispersing a water-phlegmatizing agent emulsion into a water-HMX suspension under stirring at 300 rpm and at a temperature of (85 ± 1) °C, gradually cooling at a rate of 1 °C per minute. The paper also identifies factors affecting the explosive and combustion properties of the product. The analysis results indicate that the technical specifications of the Ocfol-5.5 produced by the research group are comparable to those published abroad.